Menstrual Hygiene Management and School Absenteeism among Adolescents in Ghana: Results from a School-Based Cross-Sectional Study in a Rural Community - Mohammed, Shamsudeen; Larsen-Reindorf, Roderick Emil; Awal, Issahaku (International Journal of Reproductive Medicine, 2020)
The study aimed to deepen our understanding of the menstrual hygiene management (MHM) of adolescents and the influence of menstruation on school absenteeism. We employed a school-based cross-sectional design in five Junior High Schools combining both quantitative and qualitative data collection methods. A questionnaire was used to collect quantitative data from 250 schoolgirls, and key informant interviews were conducted with a teacher in each of the five schools. We performed logistic regression analysis to provide crude and adjusted effect estimates and 95% confidence intervals. About fifty percent of the girls were engaged in good MHM, and approximately forty percent of them reported menstrual-related school absenteeism. We did not find evidence (p=0.858) of association between MHM and menstrual-related school absenteeism. However, after controlling for the effect of other factors, we found evidence that the age of the schoolgirls, their father’s occupation, and the receipt of allowance for menstrual care products were associated with MHM. When compared to those aged 17 to 19, those aged 10 to 13 years had 0.72 (95% CI 0.21, 2.44) decreased odds of poor MHM while those aged 14 to 16 had almost 3-fold increased odds (95% CI 1.49, 4.55) of poor MHM. The adolescents whose fathers were farmers had 0.42 (95% CI 0.21, 0.82) decreased odds of poor MHM while those whose fathers were unemployed had 0.24 (95% CI 0.10, 0.61) decreased odds of poor MHM. We found that girls who did not receive regular allowance for menstrual care products had nearly 2-fold increased odds (95% CI 1.06, 3.09) of poor MHM compared to those who received allowance for menstrual care products. Menstrual pain (82.2%), fear of staining clothing (70.3%), fear of being teased (70.3%), nonavailability of sanitary pad (63.4%), and lack of private place to manage period at school (60.4%) were the common reasons cited for menstrual-related school absenteeism.